2009
DOI: 10.1111/j.1095-8649.2009.02367.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource utilization by deep‐sea sharks at the Le Danois Bank, Cantabrian Sea, north‐east Atlantic Ocean

Abstract: The feeding habits of birdbeak dogfish Deania calcea, velvet belly lantern shark Etmopterus spinax and blackmouth catshark Galeus melastomus at Le Danois Bank, Cantabrian Sea, south Bay of Biscay were studied in relation to their bathymetric distribution. Deep-sea sharks were collected during two multidisciplinary surveys carried out in October 2003 and April 2004 at the Le Danois Bank. Two different habitats were defined: (1) the top of the bank, ranging from 454 to 642 m depth and covered by fine-sand sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 58 publications
6
28
0
Order By: Relevance
“…These mesopelagic preys would be caught when the BBL remains close to the bottom, indicating the high dependence of slope demersal elasmobranchs on the pelagic ecosystem (Bizzarro et al, 2007;Rinewalt et al, 2007 ). A high dietary overlap between these two species was also reported in the Cantabrian Sea (Preciado et al, 2009) but, in contrast with the preference of E. spinax for cephalopods in our samples, that population preyed mainly on euphausiids.…”
Section: Discussionsupporting
confidence: 46%
“…These mesopelagic preys would be caught when the BBL remains close to the bottom, indicating the high dependence of slope demersal elasmobranchs on the pelagic ecosystem (Bizzarro et al, 2007;Rinewalt et al, 2007 ). A high dietary overlap between these two species was also reported in the Cantabrian Sea (Preciado et al, 2009) but, in contrast with the preference of E. spinax for cephalopods in our samples, that population preyed mainly on euphausiids.…”
Section: Discussionsupporting
confidence: 46%
“…Blue whiting is one of the most abundant fish in midwater ecosystems in the northeastern Atlantic, living mostly at depths between 100 and 600 m, although its range may extend from surface waters to beyond 1000 m depth (Heino and Godø, 2002;Hátún et al, 2007). This eurybathic species is dominant in the habitats studied and has been described as one of the keystone species for the Cantabrian Sea food web (Libralato et al, 2005;Preciado et al, 2008Preciado et al, , 2009. Moranta et al (2007) stated that the maximum abundances of N. aequalis and T. scabrus occur below 600 m in the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 95%
“…Cartes et al (1994) reported mesopelagic crustaceans to be predominant on the slope whereas benthopelagic fishes were predominant on the shelf. Prey availability on the middle slope is probably insufficient to sustain the huge biomass of planktonfeeding fishes such as blue whiting (Preciado et al, 2008), and fish feeding mainly on benthos (Preciado et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Middle Atlantic (1977)(1978)(1979)(1980) 26 - Pleuronectiformes Gray sole Glyptocephalus cynoglossus Whole St. Lawrence marine system (2004) 11 - (Mattson, 1981) 27 - (Chabot, 2010) American (Neiva et al, 2006) 4 - (Preciado et al, 2009) 8 -(Klimpel et al, 2003 Cephalopoda (Squids) Teuthida…”
Section: Peprilus Triacanthusmentioning
confidence: 99%